2010
DOI: 10.1021/jp1045707
|View full text |Cite
|
Sign up to set email alerts
|

First Principles Studies of the Effect of Nickel Carbide Catalyst Composition on Carbon Nanotube Growth

Abstract: Density functional theory calculations were used to investigate the stability of single walled carbon nanotubes (CNTs) attached to nanoparticles. The total energies and the adhesion energies between the CNTs and the nanoparticles were calculated for systems where the nanoparticles were either pure Ni or Ni carbide. It was found that the adhesion between the CNT and a pure Ni cluster is stronger than between the same CNT and a Ni-carbide cluster although the energy difference was small compared to the total adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…These calculations include DFT geometry optimization [13][14][15][16], molecular dynamics (MD) [17][18][19][20][21][22][23][24][25], and tight binding Monte Carlo (TBMC) simulations [26][27][28], in which different aspects of the CNT growth process were studied, e.g. role of carbon/catalyst/support interaction [16,19], catalyst nanoparticle state [17,18], or CNT growth with chiralities [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…These calculations include DFT geometry optimization [13][14][15][16], molecular dynamics (MD) [17][18][19][20][21][22][23][24][25], and tight binding Monte Carlo (TBMC) simulations [26][27][28], in which different aspects of the CNT growth process were studied, e.g. role of carbon/catalyst/support interaction [16,19], catalyst nanoparticle state [17,18], or CNT growth with chiralities [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Borjesson and Boltan [42] also used density functional theory calculations to study the effect of nickel carbide catalyst composition on CNT growth. Total energies and adhesion energies between CNTs and nanoparticles were calculated for systems where nanoparticles were either pure Ni or nickel carbide, as shown in Figure 6D.…”
Section: Discrete Computational Modelingmentioning
confidence: 99%
“…Borjesson and Bolton [42] used first-principles based DFT calculations to study the effect of nickel carbide catalyst composition on nanotube growth. The salient feature of this approach is that it directly gives the total energy and local adhesion energy of the system.…”
Section: Discrete Modelsmentioning
confidence: 99%
“…The supercell was 14.8 Å × 30 Å × 10 Å for the graphene sheet with the zigzag edge (72 atoms) and 17.1 Å × 30 Å × 10 Å for the graphene sheet with the armchair edge (88 atoms). Previous studies 31,42 have shown that these systems are sufficiently large to obtain valid energies and structures when atoms, molecules, or clusters are added to the edge.…”
Section: B Comparison Of Dft and Tb Structures Relevant For Swnt Andmentioning
confidence: 99%
“…The probability for catalyst encapsulation depended on the adhesion strength for temperatures larger than 600 K, and the slow carbon diffusion at lower temperatures appeared to hinder the cap formation and lift-off. Börjesson et al 31 and Page et al 32 used first principles and semi-empirical methods to show that growth may be possible from both metallic and carbide particles. Amara and co-workers studied nucleation of SWNTs on nickel nanoclusters using a tight binding (TB) Monte Carlo (MC) model, focusing on the effect of the chemical potential on the growth mechanisms.…”
Section: Introductionmentioning
confidence: 99%